Tindak Pidana Pemalsuan Dalam Pendaftaran Hak Atas Tanah dan Implikasi Hukum Penerbitan Sertifikat Yang Tidak Prosedural - Fachrul Marasabessy (Jurnal Asy-Syukriyyah, 2018)
"The issue of criminal forgery in registering land rights is an unlawful act that can cause material or immaterial losses to the actual landowner and will also have implications for non-procedural certificates issued by the National Land Agency (BPN) office, therefore professionalism in carrying out public services and administrative tasks must be carried out in accordance with the laws and regulations to be able to provide legal certainty, justice and benefit to all parties in accordance with the objectives of the law. Criminal law enforcement must still be carried out if there are indications of criminal elements involving the applicant for land rights with an officer in the land office so that public trust in the land institution can be maintained ".